Distribution and convergent validityof the Oral Hygiene Habits Scale (Revista Nacional de Odontología, 2017)
Introduction: In Mexico, the Oral Hygiene Habits Scale (ohhs) has been recently developed; its internal consistency and factorial structure have been determined, but its distribution has not been described. Aim: To describe the distribution of the ohhs and test its convergent validity. Method: A cross-sectional descriptive-correlational study with non-probability sampling was carried out. Two samples were recruited: One of 256 participants from the general population and another of 240 participants from the dental clinic. The ohhs was administered in both samples and the Simplified Oral Hygiene Index(ohi-s) only in the latter. Results: Distribution of the total ohhs score was equivalent between both samples and did not conform to a normal curve. In a range between 0 and 4, its median frequency corresponded to “sometimes.” ohhs scores between 0 and 0.999 (≤ 20 th percentile) allowed to identify poor oral hygiene habits; between 1 and 2.124, average habits; and between 2.125 and 4, good habits. These three intervals were: 0-1.749, 1.75-2.999,and 3-4 in tooth brushing; and 0-0.249, 0.25-1.249 and 1.25-4 in flossing. The correlation betweenohhs and ohi-s was negative and moderate. Conclusion: The ohhs needs to be interpreted by percentiles; its central tendency (median) shows poor oral hygiene habits among the participants, mainly due to misuse of floss; and it has convergent validity, sinceit demonstrates that poor oral hygiene habits lead to more debris and calculus.
Keywords: oral hygiene; general population; dental clinic; adults; periodontal health